BCMA-targeted CAR-T cell therapy for multiple myeloma - FAN XIAOHU; SCHECHTER JORDAN; HIRSCHMANN MICHAEL; PACAUD, LYDIA (2024)
The present application provides methods of treating a subject suffering from multiple myeloma with a suspension of chidamidyl olarenide. The present application also provides a pharmaceutical product containing the suspension of the chidazino-olarenide, an instruction for use of the suspension of the chidazino-olarenide, and a method for selling a pharmaceutical product containing a suspension of the chidazino-olarenide. 本申请提供了用西达基奥仑赛混悬液治疗患有多发性骨髓瘤的受试者的方法。本申请还提供了含有西达基奥仑赛混悬液的药物产品、西达基奥仑赛混悬液的使用说明书以及用于销售含有西达基奥仑赛混悬液的药物产品的方法。